Distribution and normalization of some metals in surface sediments from South Caspian Sea. - Sohrabi, T.; Ismail, Ahmad; Nabavi, M. B. (Springer, 2010)
Surface sediments along the south of Caspian Sea were collected to evaluate the contamination of heavy metals. The result ranged (μg/g, Fe% dw): Pb(13.06-33.48); Ni(18.01-69.63); Cd(0.62-1.5); Zn(30.11-87.88); Cu(5.86-26.37) and Fe(1.8-4%) respectively. Cadmium showed higher EF when compared to other sites. Geoaccumulation Index value for Cd in most stations was classified as moderately contaminated and moderately to strongly contaminated, as well as the average of I(geo) of Cd (1.77 ± 0.35) suggested that surface sediments of Caspian coast were moderately polluted by this metal. The result of the Pearson correlation showed that there were significant positive associations between Ni, Cd and Zn (r = 0.44-0.76; p < 0.01).